Management of post-traumatic cerebrospinal fluid (CSF) leak of anterior skull base: 10 years experience. (September 2013) - Schoentgen, Clement; Henaux, Pierre Louis; Godey, Benoit; Jegoux, Franck
Abstract Conclusion: Anterior skull base cerebrospinal fluid (CSF) leak should be surgically repaired with an endonasal approach first for less morbidity. Pretherapeutic topographical diagnosis increases the success rate of surgical repair. Objectives: We aimed to evaluate our efficiency in taking care of post-traumatic anterior skull base CSF leak, since no consensual algorithms for diagnosis and treatment have been established. Methods: Data from 40 patients treated for post-traumatic CSF leak of the anterior skull base between January 1997 and December 2008 were retrospectively reviewed. Twenty-nine patients were treated with surgery, with an endonasal approach in 14 patients and a neurosurgical approach in 15 patients. A wait and see policy was applied in 11 patients. Results: The overall risk of reccurence was 22.5%. Recurrence was represented by the presence of CSF rhinorrhea in 12.5% and the appearance of meningitis in 10% of patients. The overall risk of postoperative anosmia was 27.5%. A wait and see policy led to a higher risk of developing meningitis than surgical repair (p = 0.0003). The absence of pretherapeutic topographical diagnosis led to a higher risk of recurrence of CSF rhinorrhea (p = 0.01). The endonasal approach resulted in less postoperative anosmia (p = 0.006).